Tobacco smoke pollution from designated smoking rooms in Bangkok’s Major International Airport - Jintana Peesing (2017)
Levels of fine particulate matter with diameters of less than 2.5 microns (PM2.5), an indicator of secondhand smoke, were measured at Bangkok‟s International Airport in: 1) Designated smoking room(s) (DSR) (2) just outside these smoking rooms ,and (3) in other areas where smoking is prohibited in the main airport building. TSI SidePak AM 510 monitoring equipment was employed to monitor PM2.5 for 30 minutes/sample. PM2.5 samples were taken inside six selected DSR, just outside the same DSR and at other smoke–free areas inside the building, which included airline lounges, in the walkway to boarding gates, at arrival waiting areas, and at check–in service areas. The level of PM2.5 averaged 151.9 μg/m3 in smoking rooms, 12.0 μg/m3 just outside DSR, and 9.0 μg/m3 in areas where smoking is not allowed. PM2.5 values inside smoking rooms were fifteen times the WHO annual air quality standard of 10 μg/m3, whereas the levels outside the DSR were also elevated above the WHO standard. These findings indicate health risks in smoking rooms for travelers visiting the airport with leakage to areas just outside the DSR. Results suggest that smoking rooms at the international airport should be removed.